2010
DOI: 10.1007/s11239-010-0438-8
|View full text |Cite
|
Sign up to set email alerts
|

The oncology treatment of patients who use oral anticoagulants is connected with high risk of bleeding complications

Abstract: The data about risk for bleeding complications during anticoagulation in cancer patients with different oncology treatment are conflicting. To investigate the rate of bleeding in the course of oral anticoagulants, during treatment of malignant diseases, we conducted a retrospective study including 75 patients on stable anticoagulation prior to commencing their different oncology treatment. All patients were treated according to the consiliar decision, made based on the localization and pathohistological findin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…Active cancer has been suggested as a strong predictor of bleeding complications [6,8,14,15]. Cancer‐specific therapy is associated with bleeding complications among patients who are on chronic anticoagulation [14].…”
Section: Discussionmentioning
confidence: 99%
“…Active cancer has been suggested as a strong predictor of bleeding complications [6,8,14,15]. Cancer‐specific therapy is associated with bleeding complications among patients who are on chronic anticoagulation [14].…”
Section: Discussionmentioning
confidence: 99%
“…Treatment of cancer-associated venous thromboembolism (VTE) is challenging as the risks of recurrent VTE and bleeding complications are notably higher compared with the general VTE population. [1][2][3] In the past decade, several clinical trials have demonstrated a reduced risk of symptomatic recurrent VTE in cancer patients treated with longterm low-molecular-weight heparins (LMWH) monotherapy compared with patients receiving conventional treatment with vitamin K antagonists (VKA). [4][5][6][7] As a result, current international guidelines consider LMWH as the agent of choice in this setting.…”
Section: Introductionmentioning
confidence: 99%